Lời giải:
1.
$-3x(-4x-1)+6x(4-2x)=0$
$\Leftrightarrow 3x(4x+1)+6x(4-2x)=0$
$\Leftrightarrow 3x[4x+1+2(4-2x)]=0$
$\Leftrightarrow 3x.9=0$
$\Leftrightarrow x=0$
2.
$(-3x-1)(x-2)-(2-x)(3x-1)=11-5x$
$\Leftrightarrow (3x+1)(2-x)-(2-x)(3x-1)=11-5x$
$\Leftrightarrow (2-x)(3x+1-3x+1)=11-5x$
$\Leftrightarrow (2-x).2=11-5x$
$\Leftrightarrow 4-2x=11-5x$
$\Leftrightarrow 3x=7$
$\Leftrightarrow x=\frac{7}{3}$
3.
$x^3-3x^2+3x-1=0$
$\Leftrightarrow (x-1)^3=0$
$\Leftrightarrow x-1=0\Leftrightarrow x=1$
4.
$(2x+1)(4x^2-2x+1)-8x(x^2+2)=17$
$\Leftrightarrow [(2x)^3+1]-(8x^3+16x)=17$
$\Leftrightarrow 8x^3+1-8x^3-16x=17$
$\Leftrightarrow 1-16x=17$
$\Leftrightarrow 16x=-16$
$\Leftrightarrow x=-1$